PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 7 PEKANBARU - Komilaini '; Mahmud Alpusari; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve IPA learning outcomes the student of Class IV in SD Negeri 7 Pekanbaru through inquiry learning model application. Research motivated by the low student learning outcomes in IPA subjects. That is because the model of learning or teaching teachers to deliver material that is less varied, tends to lecture and question and answer. As the subjects in this study is the fourth grade students of SD Negeri 7 Pekanbaru school year 2015/2016 the number of students as many as 23 people consisting of 9 male students and 14 female students. The design study is Class Action Research. The stages are passed in PTK, namely: 1) Planning actions, 2) Implementation of the action, 3) observation, and 4) reflection. The results of research in the application of the implementation of inquiry learning models in science subjects is known that an increase in activity of learning at each meeting, whether the activities of teachers and students. Increased activity of the study had a positive impact on student learning outcomes are likely to increase, which increased 19% from an average score of 69.1 basis be 82.4 in the first cycle with the classical completeness 74% (not yet complete). While on the second cycle of learning outcomes obtained an increase of 33% from the average score of the base, which became 92 on average UH second cycle, with classical completeness 100% (complete). This situation shows that the improvement of learning in science subjects was successful, that application of inquiry learning models can improve IPA learning outcomes the student of class IV in SD Negeri 7 Pekanbaru.Keywords: Inquiry Learning Models, IPA Learning Outcomes